2018
DOI: 10.1186/s13287-018-1077-9
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of AKT-mTOR signal pathway enhances osteogenic/dentinogenic capacity of stem cells from apical papilla

Abstract: BackgroundStem cells from apical papilla (SCAP) are a subpopulation of mesenchymal stem cells (MSCs) isolated from the apical papilla of the developing tooth root apex of human teeth. Because of their osteogenic/dentinogenic capacity, SCAP are considered as a source for bone and dentin regeneration. However, little is understood about the molecular mechanism of osteogenic/dentinogenic differentiation of SCAP. Phosphoinositide 3 kinase (PI3K)-AKT-mammalian target of rapamycin (mTOR) signal pathway participates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…mTOR, a serine/threonine protein kinase, is a core component of mTOR complex 1 (mTORC1), the activation of which potently inhibits autophagy [26,27]. Administration of mTOR inhibitor (rapamycin) or genetic ablation of mTOR has been reported to preserve the function of osteoblasts and osteocytes, and prevent bone loss [28,29]. In addition to initiating autophagy, we also found that both CNR2 agonists suppressed mTOR signaling transduction.…”
Section: Discussionmentioning
confidence: 73%
“…mTOR, a serine/threonine protein kinase, is a core component of mTOR complex 1 (mTORC1), the activation of which potently inhibits autophagy [26,27]. Administration of mTOR inhibitor (rapamycin) or genetic ablation of mTOR has been reported to preserve the function of osteoblasts and osteocytes, and prevent bone loss [28,29]. In addition to initiating autophagy, we also found that both CNR2 agonists suppressed mTOR signaling transduction.…”
Section: Discussionmentioning
confidence: 73%
“…The AKT signaling pathway is reportedly involved in osteogenic differentiation of human mesenchymal stem cells, human dental follicle cells, and rat bone marrow stromal cells [2729]. However, AKT reportedly inhibits odontogenic differentiation of stem cells from the apical papilla [30,31]; thus, there is controversy regarding the function of AKT–mTOR signaling. The results of our study suggest that the AKT–mTOR signaling pathway is involved in the shikonin-induced odontoblastic differentiation of DPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Of the compounds that were shown to exert an inhibitory effect on NETosis, including lapatinib, carmustine, erlotinib, bosutinib, rapamycin, and nilotinib 62 , to our knowledge, only rapamycin has been studied in dentin-pulp biology. Indeed, data from one recent study indicated that this compound was able to enhance the dentinogenic capacity of stem cells in culture 63 . Clearly, further studies on the relevance of NETs and their components in pulpal inflammation are still required along with assay of the effects of novel therapeutics, which may modulate inflammatory processes and enhance dental tissue repair.…”
Section: Net Modulatorsmentioning
confidence: 99%